GENESIS OF BRECCIFORM APATITE-NEPHELINE ROCKS OF THE KHIBINY PLUTON - Fenogenov A.N.; Zenkova R.G. (My University, 1989)
The Khibiny alkalic pluton, the largest in the world, is noted for its unusual rocks, structures and associated apatite-nepheline deposits. Analyzing the genesis of the Khibiny apatite ores, various authors proposed the hypothesis of separation of immiscibility of a phosphatic from a silicate melt, but did not extend it to the brecciform ores. Their genesis was explained differently: 1) by a type of autobrecciation; 2) as a result of tectonic processes; 3) as a result of metasomatism. However, the information on brecciform apatite-nepheline rocks given here can be explained only from the standpoint of an origin by immiscibility in the magma chamber.